Formulasi Curcuma zedoaria Sebagai Emulgel Antioksidan - Yesi Desmiaty; Wiwi Winarti; Fahleni Fahleni; Lindawati Lindawati (Fakultas Farmasi Universitas Pancasila, 2020)
Curcuma zedoaria has a high antioxidant activity and potential to be made a topical antioxidant preparation. Emulgel is a combination of O/W emulsion with a gel base, and it has many advantages, including convenience in use. In this study, an emulgel formulation was made using Sepigel 305® with various concentrations (3%, 4%, and 5%). The emulgel formulation, the ethanol extract of C. zedoaria, was added with concentrations 1%, 2%, and 5%. The preparation was evaluated for physical quality and antioxidant activity using the DPPH method. In the selected formula, had been observing the accelerated stability tests were carried out for three months. Ethanol extract of C. zedoaria has antioxidant activity with IC50 49.72 ± 0.32 ppm. The best emulgel preparation is F2, which contains Sepigel 305® 4% and extract 2%. The F2 emulgel formulation was found to be stable physicochemical properties (organoleptic, homogeneity, viscosity, flow properties, dispersion ability, and emulsion type test) upon the accelerated stability tests, and pH met the requirements with antioxidant activity gave IC50 135.8 ppm. Ethanol extract of C. zedoaria can be made emulgel preparations using Sepigel 305®, physically and chemically stable, and has an excellent antioxidant activity for the three months of storage.